واقع حظر التعذيب في الجمهورية العربية السورية بين القانون الدولي والتشريعات الوطنية: دراسة تحليلية مقارنة - الهدلي، طلال; خازم، نور الدين (جامعة البعث, 2021)
يشكل حظر التعذيب في القانون الدولي لحقوق الإنسان إحدى الموضوعات بالغة الأهمية التي حظيت باهتمام كبير خلال مدة طويلة من الزمن، وبخاصة في الوقت الحالي الذي بات فيه الشغل الشاغل للمجتمع الدولي إحاطة حقوق الإنسان بالحماية الدولية الكفيلة بضمان الحقوق التي نصت عليها مختلف الوثائق الدولية بهذا الخصوص. وقد عملنا من خلال هذا البحث على دراسة واقع الحماية القانونية لحق الإنسان في عدم التعرض لأي معاملة لا إنسانية أو مهينة، أو أي صورة من صور التعذيب، أو ضروب المعاملات الأخرى التي تمس بحقه في الشرف والاعتبار، والتمتع بالكرامة الإنسانية بالنظر إلى الصفة البشرية اللصيقة بشخصه، ودون أي اعتبار آخر، إن كان على الصعيد الدولي، أو على صعيد الواقع القانوني والفعلي ضمن الحدود الإقليمية للجمهورية العربية السورية على اعتبارها من الدول الأعضاء في الاتفاقيات الدولية التي نصت على حظر التعذيب أو ممارسة أي فعل من الأفعال اللاإنسانية أو المهينة بحق الإنسان." The prohibition of torture in international human rights law is one of the most important issues that has received great attention over a long period of time, at the national and international level, especially at the present time when the concern of the international community has become to surround human rights with international protection that guarantees the rights stipulated in various international documents in this regard. We have worked through this research to study the reality of the legal protection of the human right not to be subjected to any inhuman or degrading treatment, or any form of torture, or other forms of treatment that affect his right to honor and esteem, and to enjoy human dignity by looking at the human quality attached to his person. Without any other consideration, whether at the international level, or at the level of legal and actual reality within the territorial borders of the Syrian Arab Republic, as it is a member of the international agreements that have stipulated the prohibition of torture or the practice of any inhuman or degrading act against human rights."
Keywords: حقوق الإنسان -- القوانين الدولية -- التشريعات السورية -- قانون العقوبات